Balancing Commerce and Social Responsibility in Hospitality Management: A Framework for Sustainable Tourism Practices - Dr. S. Ramesh (Journal of Social Responsibility, Tourism and Hospitality, 2024)
This research investigates the delicate equilibrium between commerce and social responsibility within the domain of hospitality management, presenting a comprehensive framework for fostering sustainable tourism practices. Drawing on empirical data, the study explores the intricate dynamics that arise when navigating the intersection of business interests and ethical considerations. The findings contribute valuable insights to the ongoing discourse surrounding sustainable practices in the hospitality sector.